Heat Transfer, Volume 1 2004
DOI: 10.1115/imece2004-59860
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Heat Conduction With Unsteady Thermal Boundary Conditions for Internal Combustion Engine Application

Abstract: Heat transfer is one major important aspect of energy transformation in spark ignition (SI) engines. Locating hot spots in a solid wall can be used as an impetus to design a better cooling system. Fast transient heat flux between the combustion chamber and the solid wall must be investigated to understand the effects of the non-steady thermal environment. This study investigates numerical simulation of 3D transient heat diffusion phenomena in solid, exposed to steady and unsteady thermal boundary conditions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As shown in Figure 4, both numerical solutions agree with the exact solution very well. Other validations and case studies can be found in [5] and will not be repeated here. …”
Section: Validationmentioning
confidence: 95%
See 3 more Smart Citations
“…As shown in Figure 4, both numerical solutions agree with the exact solution very well. Other validations and case studies can be found in [5] and will not be repeated here. …”
Section: Validationmentioning
confidence: 95%
“…From our numerical experience, the gas flow and its properties will reach periodic or close to periodic steady state within two or three engine cycles, which is feasible to solve with today's computing power. In contrast, the temperature distribution inside the metal engine components will take many more engine cycles to achieve the periodic steady state, depending on thermal penetration depth [5,12] and thermal properties of the metal components, e.g., specific heat, thermal conductivity, and density. Running the KIVA code with conjugate heat transfer mode for so many engine cycles would require massive computing power.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies, such as [16], use the onedimensional codes in order to obtain wall temperatures as boundary conditions, in order to simplify the computational domain. Along with more computational power, more and more researchers have included both the bulk gas and the solid regions in the computational domain, which means that the wall temperatures are resolved in the CFD simulation [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%